Conceptual model of brand creation worksheet for visual communication design - Anggrianto, Stevanus Christian (2020)
Communication Design students must have a set of data, information, and processes to use as a foundation for brand creation, but they often lack of this capability because there are not enough references to the brand creation process in the context of visual communication design. The identification of branding attributes and the development of a conceptual model are needed to build a brand creation tool that can help Visual Communication Design students to design a brand. To identify the attributes that designers need to create branding, an in-depth interview was conducted with six experts consisting of renowned academicians and practitioners in branding from three major Indonesian cities. The data gathered from the experts were analysed using thematic analysis resulting in four themes and 17 attributes. Then, a conceptual model of brand creation worksheet consisting of the attributes was developed and sent to the experts for verification. Next, the usability of the conceptual model was tested using experimental design research, where the conceptual model was used by the treatment group, while the control group used the standard procedure, to enable a comparison of the results between the two groups. Finally, the effectiveness and user satisfaction of the brand creation worksheet were evaluated using the end-user satisfaction questionnaire. The result indicates that the attributes and the conceptual model are usable and can be developed into a brand creation tool for Visual Communication Design. The verified conceptual model with the 17 branding attributes could be used to produce brand creation tools for brand designers